Dynamic co-culture metabolic models reveal the fermentation dynamics, metabolic capacities and interplays of cheese starter cultures - TOKSOY ÖNER, EBRU (WILEY, 2021)
In this study, we have investigated the cheese starter culture as a microbial community through a question: can the metabolic behaviour of a co-culture be explained by the characterized individual organism that constituted the co-culture? To address this question, the dairy-origin lactic acid bacteriaLactococcus lactissubsp.cremoris,Lactococcus lactissubsp.lactis,Streptococcus thermophilus andLeuconostoc mesenteroides, commonly used in cheese starter cultures, were grown in pure and four different co-cultures. We used a dynamic metabolic modelling approach based on the integration of the genome-scale metabolic networks of the involved organisms to simulate the co-cultures. The strain-specific kinetic parameters of dynamic models were estimated using the pure culture experiments and they were subsequently applied to co-culture models. Biomass, carbon source, lactic acid and most of the amino acid concentration profiles simulated by the co-culture models fit closely to the experimental results and the co-culture models explained the mechanisms behind the dynamic microbial abundance. We then applied the co-culture models to estimate further information on the co-cultures that could not be obtained by the experimental method used. This includes estimation of the profile of various metabolites in the co-culture medium such as flavour compounds produced and the individual organism level metabolic exchange flux profiles, which revealed the potential metabolic interactions between organisms in the co-cultures.
Keywords: lactic acid bacteria; starter cultures; genome-scale metabolic network; co-culture metabolic modelling; LACTIC-ACID BACTERIA; FLUX BALANCE ANALYSIS; LACTOCOCCUS-LACTIS; STREPTOCOCCUS-THERMOPHILUS; DIACETYL PRODUCTION; FOOD FERMENTATIONS; FLAVOR FORMATION; GROWTH; LEUCONOSTOC; REQUIREMENTS